Digital Transformation and Governance Reform in Indonesian Cooperatives: A Systematic Literature Review Analysis toward Vision 2045 - Tomy Wijaya; Fatimah Alauwiyah (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
This paper examines governance challenges in the digital transformation of cooperatives in Indonesia and their implications for strengthening cooperative institutions in the digital economy. The research aims to analyse the relationship between governance structures and cooperative digitalisation and to identify strategic directions for strengthening digital cooperatives in support of Vision 2045. The paper uses a qualitative approach, drawing on a systematic literature review of academic publications, policy documents, and institutional reports on cooperative governance and digital transformation. The findings show that the success of cooperative digitalisation is influenced by three key factors: adaptive governance frameworks, supportive regulations that accommodate digital innovation, and improved digital literacy among cooperative members and managers. In addition, the development of an inclusive digital ecosystem is essential to facilitate the integration of digital technologies in cooperative management, services, and member participation. These results highlight that governance reform and digital capacity building are fundamental prerequisites for accelerating cooperative digital transformation. However, this study is limited to literature-based analysis and does not capture empirical variations in local cooperative practices. Therefore, future research should employ empirical approaches, such as case studies or surveys, to evaluate the effectiveness of digital cooperative governance and its impact on member welfare and regional economic development.